Long-Range Temporal Correlations of Patients in Minimally Conscious State Modulated by Spinal Cord Stimulation - Liang, Zhenhu; Li, Jiani; Xia, Xiaoyu; Wang, Yong; Li, Xiaoli; He, Jianghong; Bai, Yang (Frontiers in Physiology, 2018)
Abstract: Objective: It has been demonstrated that the Spinal Cord Stimulation (SCS) can ameliorate the consciousness level of patients with disorder of consciousness (DOC). However, the underlying mechanisms of this stimulation have not yet been clarified. This study was to investigate the complex neuronal dynamics in electroencephalogram (EEG) during the SCS intervention in minimally conscious state (MCS) patients. Methods: Resting-state EEG were recorded from sixteen MCS patients pre- and post- SCS. A Genuine Detrended Fluctuation Analysis Exponent (GDFAE) was proposed and employed to measure the long-range temporal correlations (LRTCs) in five EEG frequency bands (delta(1-4Hz), theta(4-8Hz), alpha(8-13Hz), beta(13-30Hz) and gamma(30-45Hz)). The surrogate analysis based on the Fourier phase randomization was utilized to determine the significance of LRTCs. The GDFAE were analyzed in four brain regions (frontal, central, posterior and occipital) at each frequency band. Results: The GDFAE values were mainly range from 0.5 to 1 and showed temporal and spatial variations between pre-SCS and post-SCS state. After the SCS, the values of GDFAE significantly increased in frontal area at delta (p<0.001), theta (p<0.05) and alpha (p<0.001) band. In theta band, there was also significantly increase of GDFAE in occipital area (p<0.001). No significant change was found in beta and gamma bands in any brain regions. Conclusion: The enhanced LRTCs (increased GDFAE indices) in delta, theta and alpha bands suggested that the SCS affects the brain dynamics and enhanced the capacities for extensive temporal integration in low frequency oscillations and then to accommodate the consciousness. We conjectured that the long-range temporal dependence of neural activity at low frequency bands particular in the frontal region were enhanced effectively by the SCS modulation. Significance: The GDFAE is a promising new brain complex dynamic measure for investigating the neurophysiologic mechanisms of SCS in the DOC patients. Keywords: Spinal cord stimulation, MCS, EEG, long range temporal correlations, Detrended Fluctuation Analysis